The association of pelvic organ prolapse severity and improvement in overactive bladder symptoms after surgery for pelvic organ prolapse - Kim, Mi Sun; Lee, Gee Hoon; Jang, Ji Hyon; Kim, Hyeon Chul (Obstetrics & gynecology science, 2016)
The purpose of this study was to evaluate the impact of pelvic organ prolapse (POP) repair on overactive bladder (OAB) symptoms in women with POP and the effect of baseline POP severity on improvement in OAB after surgical repair of POP. And we also tried to identify any preoperative factors for persistent postoperative OAB symptoms. A total of 87 patients with coexisting POP and OAB who underwent surgical correction of POP were included and retrospectively analyzed and postoperative data was obtained by telephone interview. OAB was defined as an affirmative response to item no. 15 (urinary frequency) and item no. 16 (urge incontinence) of the Pelvic Floor Distress Inventory. POP severity was dichotomized by Pelvic Organ Prolapse Quantification stage 1 to 2 (n=22) versus stage 3 to 4 (n=65). OAB symptoms were significantly improved after surgical treatment (P<0.001). But there was no significant differences in postoperative improvement of frequency and urge incontinence between stage 1 to 2 group versus stage 3 to 4 group. Preoperative demographic factors (age, parity, and POP stage) were not significantly related to persistent postoperative OAB symptoms. Women with coexisting POP and OAB who undergo surgical repair experience significant improvement in OAB symptoms after surgery, but severity of POP had no significant difference in improvement of OAB symptoms. Postoperative persistent OAB symptoms were not related to age, parity, body mass index, and POP stage.